Chloroplast-Specific in Vivo Ca2+ Imaging Using Yellow Cameleon Fluorescent Protein Sensors Reveals Organelle-Autonomous Ca2+ Signatures in the Stroma. Issue 4 (1st June 2016) - Loro, Giovanna; Wagner, Stephan; Doccula, Fabrizio Gandolfo; Behera, Smrutisanjita; Weinl, Stefan; Kudla, Joerg; Schwarzländer, Markus; Costa, Alex; Zottini, Michela
Abstract : Plants expressing a chloroplast-localized Cameleon Ca 2+ probe allow single-organelle analysis of chloroplast Ca 2+ dynamics. Abstract: In eukaryotes, subcellular compartments such as mitochondria, the endoplasmic reticulum, lysosomes, and vacuoles have the capacity for Ca 2+ transport across their membranes to modulate the activity of compartmentalized enzymes or to convey specific cellular signaling events. In plants, it has been suggested that chloroplasts also display Ca 2+ regulation. So far, monitoring of stromal Ca 2+ dynamics in vivo has exclusively relied on using the luminescent Ca 2+ probe aequorin. However, this technique is limited in resolution and can only provide a readout averaged over chloroplast populations from different cells and tissues. Here, we present a toolkit of Arabidopsis ( Arabidopsis thaliana ) Ca 2+ sensor lines expressing plastid-targeted FRET-based Yellow Cameleon (YC) sensors. We demonstrate that the probes reliably report in vivo Ca 2+ dynamics in the stroma of root plastids in response to extracellular ATP and of leaf mesophyll and guard cell chloroplasts during light-to-low-intensity blue light illumination transition. Applying YC sensing of stromal Ca 2+ dynamics to single chloroplasts, we confirm findings of gradual, sustained stromal Ca 2+ increases at the tissue level after light-to-low-intensity blue light illumination transitions, but monitor transient Ca 2+ spiking as a distinct and previously unknown component of stromal Ca 2+ signatures. Spiking was dependent on the availability of cytosolic Ca 2+ but not synchronized between the chloroplasts of a cell. In contrast, the gradual sustained Ca 2+ increase occurred independent of cytosolic Ca 2+, suggesting intraorganellar Ca 2+ release. We demonstrate the capacity of the YC sensor toolkit to identify novel, fundamental facets of chloroplast Ca 2+ dynamics and to refine the understanding of plastidial Ca 2+ regulation.